2019
DOI: 10.1136/ijgc-2019-000604
|View full text |Cite
|
Sign up to set email alerts
|

Gestational trophoblastic neoplasia: a meta-analysis evaluating reproductive and obstetrical outcomes after administration of chemotherapy

Abstract: IntroductionGestational trophoblastic neoplasia represents a rare placental malignancy spectrum that is treated with single- or multi-agent chemotherapy. This disease often impacts women of childbearing age, making post-chemotherapy fertility and obstetrical outcomes an important consideration. We aimed to ascertain the pregnancy rates and obstetric outcomes in women with gestational trophoblastic neoplasia after undergoing treatment with chemotherapy.MethodsA systematic literature review was conducted to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
2
10
1
2
Order By: Relevance
“…Another larger study of 320 subjects examining reproductive outcomes after floxuridine-based regimens at our center found that 97.8% successfully became pregnant [32]. A meta-analysis evaluating reproductive outcomes after chemotherapy for GTN revealed a pregnancy rate of 86.7% among those desiring children, with a malformation rate of 1.76% [33]. Therefore, our data demonstrated that the reproductive outcomes post-FAEV are comparable to other regimens.…”
Section: Discussionsupporting
confidence: 58%
“…Another larger study of 320 subjects examining reproductive outcomes after floxuridine-based regimens at our center found that 97.8% successfully became pregnant [32]. A meta-analysis evaluating reproductive outcomes after chemotherapy for GTN revealed a pregnancy rate of 86.7% among those desiring children, with a malformation rate of 1.76% [33]. Therefore, our data demonstrated that the reproductive outcomes post-FAEV are comparable to other regimens.…”
Section: Discussionsupporting
confidence: 58%
“…A sub-group analysis among all treated women demonstrated a statistically significant lower pregnancy rate after multi-agent chemotherapy than after single-agent chemotherapy (OR=0.54, 95% CI 0.38 to 0.77, p=0.001). 40 Blagden et al found higher conception rates in women in the single-agent group who conceived within a year after completion of treatment, 36 while no difference in pregnancy rate between single-or multi-agent chemotherapy was found in a recent MITO-9 analysis. 31 Studies comparing pregnancies in women who conceived within 6 months after completion of chemotherapy with those who conceived later, noted a higher rate of spontaneous abortions in early conceptions.…”
Section: Fertility and Reproductive Outcomes After Single-agent Chemomentioning
confidence: 96%
“…Studies in the literature support a high pregnancy rate despite prior chemotherapy with no increased adverse outcomes. 1,9,12 Furthermore, as previously demonstrated, women of childbearing age were able to get pregnant after uterine arteries embolization, [13][14][15] this management was adopted when the patient was found having severe hemorrhage episodes over the chemotherapy.…”
Section: Discussionmentioning
confidence: 89%